American Agriculture: Schultz' Analysis and Policy Proposals - Davis, Joseph S. (The Review of Economics and Statistics, 1947)
rT W. SCHULTZ and his circle have been making penetrating analysis of agricultural conditions, problems, and policies, showing unusual awareness of the whole national economy, of evolving knowledge over a wide range, and of advances in general economic thought. Their works, properly referred to frequently in Schultz' meaty one here reviewed,' deserve the respectful attention of economists, whether specialists in or not. The present stimulating contribution, evolved from a mimeographed draft that was widely circulated for comments, especially challenges discriminating examination by serious students. To a degree that I cannot adequately indicate in detail, much of its content strikes me as excellent. Many positions are well taken on broad and specific issues on which much divergence of opinion exists. Some new ground is broken, e.g., on income-elasticity of demand. Yet the book is not thorough, well matured, and authoritative. It is marred by defects of organization, excessive repetition, and various omissions and obscurities. I find puzzling the author's peculiar or inconsistent usage of terms, such as durable goods, returns, political economy, economic progress, and even There are many slips, and numerous statements to which exception should be taken. On a few important matters, moreover, Schultz seems to me either wrong or on insecure ground. To argue all these points fully is out of the question, but it seems appropriate to present a liberal sample, of course without claiming that my own position is invariably right. Agriculture in Unstable Economy is one of the research studies sponsored by the Committee for Economic Development, in a group dealing with long-term fundamental problems. The title fails to suggest that the book deals almost solely with the American economy, with only incidental references to others. In referring to the economy as unstable, 2 Schultz means merely dynamic, expanding and fluctuating. He evidently expects both expansion and sizable business fluctuations to continue: maintenance of high-level employment is a very worthy goal but one uncertain if not unlikely to be achieved (pp. 2 I9-20). In his Foreword, T. 0. Yntema calls the book an analysis of the essential conditions for a healthy, prosperous agriculture. Schultz says in his own Preface: Its main purpose is to lay the foundations for a [revised? ] national with regard to agriculture. 3 In my view, the book falls short of achieving these highly ambitious aims. When he comes to Part IV, Schultz overmodestly describes his constructive chapters as essentially a series of notes on problems in policy (p. I86). He deliberately gives only incidental attention to problems within agriculture in order to devote primary attention to between problems, to the functions of in the political [!] economy